Assessment of the environmental capability of Tabriz city in the formation of a creative city - Shahrzad Amirsarvari; Mohammad Ebrahim Ramazani (تحقیقات کاربردی علوم جغرافیایی)
The creative city will make all your try and relying to the idea of people to solve their problems and build a city of people who are looking for their desired cities. The creative city is not only a space in which creativity grows, but organizing and managing it is creatively planned. The title and general purpose of this research is the assessment of the environmental capability of Tabriz city in the formation of a creative city , Tabriz is one of the main cities of the country and among the major centers of urbanization in Iran, which is the center of East Azerbaijan province and in comparison with the center of neighboring provinces in terms of quantitative (such as population) and Quality (such as functions) has a speed positions index and is far higher in the surface. Accordingly, in this thesis at first the theoretical  foundations related to the subject has been expressed and the research method and data collection is a field and library. The statistical population of the research (using Morgan table) was 384 population of Tabriz, which was conducted through a stratified random sampling questionnaire. Validity and reliability of the questionnaire were determined by content validity and formal validity and calculating Cronbach's alpha confirmation. The results of the study showed that environmental power as well as social and social activities on the formation of creative city has a positive and significant effect on the formation of creative city. The results of this study show that tabriz city does not have the environmental power needed for the formation of creative city.